EDUCATION OF EMOTIONS BASED ON NATIONAL VALUES OF PRIMARY CLASS STUDENTS IN THE PROCESS OF PHYSICAL EDUCATION - Tulepbayevna, Kuttibekova Guljan (Journal of Learning on History and Social Sciences, 2024)
The topic of ways to instill feelings based on national values in the process of physical education of primary school students is one of the current problems. However, through physical education we understand the inculcation of such national values as nationalism, patriotism, loyalty to the Motherland, pride in one’s nation, protection of its honor in international arenas and at the same time respect for representatives of other nations. nation. Raising students to be healthy, independent, energetic individuals, especially starting from the primary grades, is considered one of the pressing tasks of our time